Exploring MNCs supply chain challenges in the bottom of the Pyramid (BoP) market - Irteza, Ali (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020..